Prevalence of detectable viral load and its associated factors among adult patients receiving ART in Choma District, Zambia - Macwani Mutukwa; Patrick Kaonga; Christine Mfula; Musa M. Mwansa; Benson M. Hamooya (PLoS ONE, 2025)
Background Africa accounts for two-thirds of the global HIV infection and a disproportionate burden is in sub-Saharan Africa. In 2017, the Zambian government launched the U = U campaign which has proven to be key in the prevention of HIV. However, there is a paucity of empirical evidence on the magnitude of detectable viral load in Choma district. This study aimed to estimate the proportion of detectable viral load and identify the associated factors among adults living with HIV receiving antiretroviral therapy (ART) in Choma District, Zambia. Methods This was a cross-sectional study among adults aged 15 years and older on ART ≥ 12 months. Sociodemographic, clinical and laboratory data were collected through a structured questionnaire and data collection form for secondary data from medical records. Detectable Viral load (primary outcome) and Virological failure (secondary outcome) were defined as viral load (VL) > 200cp/ml and VL > 1000cp/ml respectively. The data collected was then analysed using STATA version XII. Descriptive statistics, chi-square test, Wilcoxon rank sum test, and logistic regression were the statistical methods used. Results There was a total of 448 participants. The median (interquartile range (IQR)) age was 41 years (32, 49) of whom 284 (63.2%) were females. The prevalence of detectable and virological failure were 10.3% (n = 46; 95% confidence interval (CI) 7.6, 13.5) and 5.4% (n = 24; 95%CI 3.5, 7.9) respectively. In multivariable analysis, detectable VL was significantly associated with young age (16 – 24 years) (odds ratio (OR) 3.38; 95%CI 1.04, 10.94; p = 0.042), no formal education (OR 3.32; 95%CI 1.06, 10.40; p = 0.040), missing medication (OR 3.99; 95%CI 1.83, 8.73; p = 0.001) and problem taking medication (OR 2.74; 95%CI 1.10; 6.84; p < 0.030); while factors associated with virological failure were being in age group 16 – 24 years (OR 7.28; 95%CI 1.62, 32.68, p = 0.009), male gender (OR 3.12; 95%CI 1.25, 7.76; p = 0.014), Missing taking medication (OR 8.28; 95%CI 2.59, 26.40; p < 0.001) and taking dolutegravir-based regimen with zidovudine/lamivudine backbone (OR 17.80 95% CI 2.29 - 132.31; p = 0.005). Conclusion Detectable VL and virological failure were prevalent among adults receiving ART for ≥ 12 months and were significantly associated with sociodemographic and clinical factors. There is a need for targeted interventions, especially among young people and males to accelerate the attaining of the last 95 of the UNAIDS target; which is imperative in the prevention of HIV transmission. Qualitative research which aims to get an in-depth understanding of why men and young people do not attain optimal viral suppression is encouraged.